Internal Branding : Developing a Predictive Model for the Indian Service Sector - Sehgal, Pooja; Kaushal, Sarika; Sagar, Mahim (Indian Journal of Marketing, 2022)
The purpose of this paper was to develop a predictive model to explain the internal brand building phenomenon in service sector organizations from the banking, IT, and health sectors. This research applied the grounded theory methodology to identify the factors that had a critical role in the internal branding outcomes. Total interpretive structural modeling or TISM was conducted to determine the hierarchy and interlinkages among these factors. Further one-way ANOVA analysis was conducted to study whether the factors identified were relevant in the same manner across service sectors. Finally, internal branding factors were empirically validated. The major factors identified are: Organization Size, Change or Continuity, Marketing Approach, Organizational Empathy, Organizational Protocols, Customer Connect, Industry Potential, and Internal Branding Tools. The findings of the TISM framework provided a clear understanding of the interplay between the management style and the degree of empathy toward the staff, and both these factors impacted the outcome of the overall marketing approach, customer connect, and also internal branding tools. Several significant managerial implications are drawn from this study. It provided suggestions on how to factor in a specific context, complexity, and attributes of organizations as they develop their internal branding strategy and how best to integrate the same with the brand values and their external marketing efforts.